Analisis Keterampilan Sepak Takraw Siswa Usia 13-15 Tahun Smp Negeri 4 Di Kecamatan Semidang Alas Kabupaten Seluma - Zozan Pauzi; Dolly Apriansyah; Martiani Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to describe the analysis of Sepak Takraw skills of students aged 13-15 years in Semidang Alas District, Seluma Regency. This is a quantitative descriptive study. The method used is a survey. The population of this study was 15 male students at SMP Negeri 04 Seluma that there were 5 male students with a percentage (33.4%) who had a Sepak Mula smash in the Sepak Takraw game with a very good category. While those who had a Sepak Mula smash in the Sepak Takraw game were 10 people with a percentage of 66.6% with a good category while the category was sufficient with a percentage of 0% who had a Sepak Mula smash in the Sepak Takraw game categorized as moderate. For those who had a Sepak Mula smash in the Sepak Takraw game at SMP Negeri 04 Seluma, there were less than no people with a percentage of 0% and very less than none. When viewed from the frequency of each category, it is seen that the Sepak Mula smash in the Sepak Takraw game at SMP Negeri 04 Seluma for 15 male students at SMP Negeri 04 Seluma is